1980
DOI: 10.1021/j100462a009
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and mechanism for the catalytic oxidation of sulfur dioxide on carbon in aqueous suspensions

Abstract: Combustion-produced soot (carbonaceous) particles have been found to be efficient catalysts for so 2 oxidation, especially in the presence of liquid water. A kinetic study of the catalytic oxidation of so 2 on carbon particles suspended in solution has been carried out. The reaction was found to be first order with respect to tlte concentration of carbon particles, 0.69th order with respect to dissolved oxygen, between zero and second order with respect to S(IV) concentrations, and independent of the pH. Tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
1

Year Published

1981
1981
2010
2010

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 69 publications
(41 citation statements)
references
References 3 publications
0
40
1
Order By: Relevance
“…From the evidence presented so far, we are inclined to hypothesize that the rapid S0 2 oxidation observed in the morning period is caused by incomplete combustion products in the presence of liquid water droplets (Brodzinsky et al, 1980;Chang et al, 1981;Novakov, 1984;Benner et al, 1985). Field evidence supporting this hypothesis was obtained by Eatough et al (1984), who observed rapid sulfate formation when the plume of an oil-burning power plant impacted on a fog bank.…”
Section: Resultsmentioning
confidence: 98%
“…From the evidence presented so far, we are inclined to hypothesize that the rapid S0 2 oxidation observed in the morning period is caused by incomplete combustion products in the presence of liquid water droplets (Brodzinsky et al, 1980;Chang et al, 1981;Novakov, 1984;Benner et al, 1985). Field evidence supporting this hypothesis was obtained by Eatough et al (1984), who observed rapid sulfate formation when the plume of an oil-burning power plant impacted on a fog bank.…”
Section: Resultsmentioning
confidence: 98%
“…The mechanism and kinetics of the stage II process have been studied in detail (ref. 17), and its significance in atmospheric sulfate formation has been assessed (refs.18,19). This second stage process cannot fully explain by itself the observed regularities for ambient sulfate.…”
Section: Introductionmentioning
confidence: 99%
“…Novakov et al (1974) observed that sulfate formed when soot particles were exposed to so 2 and that the sootcatalyzed reaction was enhanced at increased relative humidity. In other studies in our laboratory, Brodzinsky et al (1980) showed that sulfite was oxidized to sulfate by aqueous suspensions of activated carbon, acetylene soot, and natural gas soot. Their flask-type reactions showed that the rate of oxidation was independent of pH when pH < 7.6.…”
Section: Introductionmentioning
confidence: 72%
“…The flask-type reactions with aqueous suspensions of soot were described earlier (Brodzinsky et al, 1980) and the procedures are summarized here.…”
Section: Introductionmentioning
confidence: 99%